FOXD1 is associated with poor outcome and maintains tumor-promoting enhancer–gene programs in basal-like breast cancer - Kumegawa, Kohei; Yang, Liying; Miyata, Kenichi; Maruyama, Reo (Frontiers in Oncology, 2023)
Breast cancer biology varies markedly among patients. Basal-like breast cancer is one of the most challenging subtypes to treat because it lacks effective therapeutic targets. Despite numerous studies on potential targetable molecules in this subtype, few targets have shown promise. However, the present study revealed that FOXD1, a transcription factor that functions in both normal development and malignancy, is associated with poor prognosis in basal-like breast cancer. We analyzed publicly available RNA sequencing data and conducted FOXD1-knockdown experiments, finding that FOXD1 maintains gene expression programs that contribute to tumor progression. We first conducted survival analysis of patients grouped via a Gaussian mixture model based on gene expression in basal-like tumors, finding that FOXD1 is a prognostic factor specific to this subtype. Then, our RNA sequencing and chromatin immunoprecipitation sequencing experiments using the basal-like breast cancer cell lines BT549 and Hs578T with FOXD1 knockdown revealed that FOXD1 regulates enhancer–gene programs related to tumor progression. These findings suggest that FOXD1 plays an important role in basal-like breast cancer progression and may represent a promising therapeutic target.